Pros and Cons of Military-Based Character Education: A Critical Discourse Analysis of Fairclough’s Framework - Lewi Kabanga'; Robinhot Sagala; Santy Layan; Dorce Bu’tu (Hasanuddin University, 2025)
This study investigates the ideological contestations embedded in public discourse regarding the West Java Governor’s policy on character education in military barracks. Adopting Norman Fairclough’s Critical Discourse Analysis (CDA) framework, data were collected from eleven public figures representing diverse institutional backgrounds, whose statements were disseminated through major Indonesian online media outlets (Kompas, Detik, Tempo, NU-Online, Gesuri.id, CNN Indonesia, Liputan6) and YouTube. The findings reveal that pro-policy discourse predominantly employed legitimizing diction, affirmative modalities, and metaphors that framed military barracks as spaces for discipline and nation-building. Conversely, counter-discourse highlighted risks of child rights violations, psychological harm, and incompatibility with inclusive and holistic educational principles. These opposing discourses demonstrate intertextual practices ranging from legal references to cultural values, while also reflecting broader ideological struggles between state-driven discipline-oriented education and civil society’s advocacy for democratic, child-centered learning. The study contributes to CDA scholarship by extending its application to the underexplored domain of military-based character education in Indonesia and offers insights into how power and ideology shape the trajectory of educational policy debates.